2012
DOI: 10.3113/fai.2012.0591
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Features of Osteochondral Lesions of the Talus

Abstract: This study refutes traditional teachings regarding the location of OLT and supports recent studies showing that most lesions are located medially and centrally on the talar dome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 26 publications
1
18
0
2
Order By: Relevance
“…Mechanical or functional instability and locking may or may not be present and the clinical findings often remain non-specific 4. In the setting of chronic ankle pain, particularly with the insensitivity of plain radiography for subtle changes,5 MRI has both a high sensitivity and specificity for osteochondral lesions and can assist with prognosis and treatment 1 2 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical or functional instability and locking may or may not be present and the clinical findings often remain non-specific 4. In the setting of chronic ankle pain, particularly with the insensitivity of plain radiography for subtle changes,5 MRI has both a high sensitivity and specificity for osteochondral lesions and can assist with prognosis and treatment 1 2 6…”
Section: Discussionmentioning
confidence: 99%
“…Isolated, diffuse high-signal within the subchondral and cancellous bone on fluid-sensitive sequences is not indicative of an acute lesion or oedema, but is referred to as ‘oedema-like signal’. This isolated high-signal can represent a healing response, increasing instability, necrosis, fibrosis or trabecular injury 1 2 6…”
Section: Discussionmentioning
confidence: 99%
“…Исследование, основанное на изучении МРТ данных, проведенное Hembree с соавт. [14], определило, что большинство выявляемых локализаций остеохондральных повреждений таранной кости располагались медиально и центрально [15]. Независимо от этого, латеральная локализация данных повреждений связана с травмой от 93% до 98% случаев.…”
Section: анатомия и патофизиологияunclassified
“…41,42 In addition, obtaining a CT scan of the ankle in full plantarflexion has been shown to be a reliable method for determining access to the talar dome through anterior arthroscopy, and efforts to quantify this have shown that 48.2% of the medial talar dome and 47.8% of the lateral talar dome in the sagittal dimension is accessible anterior to the anterior distal tibial rim with the ankle in full plantarflexion. Recent studies have demonstrated that up to 55% of OLTs are located medially and centrally, and 31% are located laterally and centrally on the talar dome.…”
Section: Preoperative Planningmentioning
confidence: 99%